Dunite´s different uses in the metallurgic industry in Cuba - Pons-Herrera, José Alberto; Leyva-Rodríguez, Carlos Alberto (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
The dunite is a basic rock formed mainly by magnesitic silicates (dunites serpentinized) and is distributed throughout  the Moa region, Holguín, Cuba.  The purpose is the dunites use as anti-adherent painting, moulding sand and for male moulds, taken into account the results reached in the different tests made at an  industrial scale in the Union of Nickel in Moa’s smelting factory. This investigation made for the first time in Cuba, shows that the dunites are common material reserves that they are used traditionally, but that in the future can be exhausted in the future.